Sustainability assessment : context of resource and environmental policy - Ali, Mohammad (Academic Press, 2013)
Sustainability Assessment is a comprehensive compilation of all the known policy factors related to sustainability. This book outlines all of the elements and considerations of community aspects of policy evaluation in an effort to reduce the future consequences on resources and environmental sustainability. The basic assumption behind it is that sustainability, though oriented to resources and meeting demands, starts from formulation of policy. Policies are so interrelated that all policies have some roles to play toward sustainability. Helps policymakers integrate the objectives of sustainability into policy actions in a given socio-political environment and plan a strategy for policy implementation. Includes some policy factors that have not been discussed in other texts.